Anger-related problems and sleep disturbances in adolescents playing massively multiplayer online role-playing games - GÜNDOĞDU, ÜMMÜGÜLSÜM (My University, 2023)
Purpose: Publications have shown that playing massively multiplayer online role-playing games (MMORPGs) can increase the risk of depression, social withdrawal, and anxiety. In the current study, we compared adolescents who play MMORPGs to those who do not on anxiety and depression symptoms, sleep disturbances, and anger-related problems. Methods: The participants included 52 adolescents (aged 12–18 years) who play MMORPGs and a control group of age and gender-matched adolescents. Subjects completed the State-Trait Anger Scale (STAXI), Children’s Depression Inventory (CDI), Pittsburgh Sleep Quality Index (PSQI), and Screen for Child Anxiety Related Emotional Disorders Child Version (SCARED) questionnaires. Results: Anxiety, depressive symptoms, and anger-related problems were higher in adolescents who played MMORPGs than those who did not. The scores of trait anger, anger in, and anger-out subscales showed a positive correlation with the CDI scores, while the anger control scores showed a negative correlation (p < 0.05). Subjective sleep quality, sleep disturbances, sleep functionality subscale, and total PSQI scores of adolescents who played MMORPGs showed a significant relationship with SCARED scores (p < 0.05). The sleep latency showed a positive correlation with the scores on CDI scales. Conclusions: Consequently, as anxiety problems increase, subjective sleep quality decreases, frequent sleep disturbances impair adolescents\" daily functioning and the risk of sleep disturbances increases in adolescents who play MMORPGs. In addition, an increase in depressive symptoms prolongs sleep latency and decreases total sleep time. When depressive symptoms increase in adolescents who play MMORPGs, they also have more anger problems.
Keywords: Tıp; Dahili Tıp Bilimleri; Nöroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Neurology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Psikiyatri; KLİNİK NÖROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; PSYCHIATRY; CLINICAL NEUROLOGY; Yaşam Bilimleri; Nöroloji (klinik); Psikiyatri ve Ruh Sağlığı; Life Sciences; Neurology (clinical); Psychiatry and Mental Health; Adolescents; Anxiety; Depression; Massively multiplayer online role-playing games; Sleep problems